2003
DOI: 10.1155/2003/268528
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Patients Investigated for Elevated Liver Enzymes

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common diagnosis among patients referred to gastroenterology and hepatology clinics for the evaluation of elevated liver enzymes. The diagnosis of NAFLD is supported by blood work to exclude other liver diseases, and by ultrasound evidence of fat in the liver in patients without a significant history of alcohol intake. The gold standard, however, is a liver biopsy to show the typical histological features of NAFLD, which are almost identical to those of alcohol-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…23,28 Further, the histological features reported in these studies are less severe compared to those in the West, where advanced fibrosis or cirrhosis has been reported in up to 50% of NAFLD cohorts. 9,31,51,52 This is possibly because these patients do not represent the general population with NAFLD, as they have greater dysglycaemia and obesity. Two recent studies also support this contention and have paradoxically reported advanced fibrosis (3/4) in only 6%-7% of patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…23,28 Further, the histological features reported in these studies are less severe compared to those in the West, where advanced fibrosis or cirrhosis has been reported in up to 50% of NAFLD cohorts. 9,31,51,52 This is possibly because these patients do not represent the general population with NAFLD, as they have greater dysglycaemia and obesity. Two recent studies also support this contention and have paradoxically reported advanced fibrosis (3/4) in only 6%-7% of patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] A separate informed consent for liver biopsy was required. Patients were proposed for transjugular liver vein catheterization and biopsy whenever this was possible from a logistic point of view.…”
Section: Methodsmentioning
confidence: 99%
“…The 100 WAT signature genes were disproportionately elevated with aging in WT mice ( P = 2.59 × 10 −20 ; Figure 6A), consistent with age-related steatosis [33]. WAT-specific genes were also elevated with aging in KO mice, but this trend was weaker compared to WT mice ( P = 2.15 × 10 −5 ; Figure 6B).…”
Section: Resultsmentioning
confidence: 70%
“…This prompted us to ask whether development of steatosis with aging is diminished in KO mice [33]. A microarray dataset (GSE46209) [34] was therefore used to identify genes with significantly greater expression in intra-abdominal white adipose tissue (WAT; n = 3) compared to liver ( n = 3) (C57BL/6 mice; age 6-8 weeks).…”
Section: Resultsmentioning
confidence: 99%